NEW FRONTIERS OF HUMAN RIGHTS: CULTURAL HERITAGE, CULTURAL RIGHTS AND MULTILEVEL CONSTITUTIONALISM - Burckhart, Thiago Rafael (Revista Direitos Culturais, 2024)
Cultural rights are currently assuming a new facet in human rights law and theory. Cultural heritage is entrenched at the center of this phenomena, spanning from the tangible dimension to others emerging in the last decades. It implies the recognition of a new right in a multilevel perspective: the right to cultural heritage, that encompasses justiciability, citizen participation and access to cultural heritage, complexifying the institutional symbolic negotiation over cultural heritage nowadays. This article aims to analyze the emergence of the right to cultural heritage as a human and fundamental right, in multilevel legal dynamics. To this end, it will focus on the developments within international law and the Brazilian case, which is paradigmatic in comparative studies on the subject, especially when it comes to constitutional protection of cultural rights. The article is methodologically grounded in the fields of legal and constitutional theory, as well as human and fundamental rights theory, in as interdisciplinary outlook and hypothetical-deductive approach. It was verified that cultural rights and cultural heritage are new frontiers in human and fundamental rights law. Indeed, the recognition of a “right” to cultural heritage requires the elaboration of new theoretical and empirical approaches as well as new legal methods in order to guarantee justiciability, participation and access to it. The Brazilian case is paradigmatic in this regard, as it constitutionally provides for judicial mechanisms and the provision for participation, enshrining a “heritage-rights approach”, in a multilevel dialogue.